Reproducibility of corticospinal diffusion tensor tractography in normal subjects and hemiparetic stroke patients - Lin, Chao-Chun; Tsai, Miao-Yu; Lo, Yu-Chien; Liu, Yi-Jui; Tsai, Po-Pang; Wu, Chiao-Ying; Lin, Chia-Wei; Shen, Wu-Chung; Chung, Hsiao-Wen (European journal of radiology, 2013)
The reproducibility of corticospinal diffusion tensor tractography (DTT) for a guideline is important before longitudinal monitoring of the therapy effects in stroke patients. This study aimed to establish the reproducibility of corticospinal DTT indices in healthy subjects and chronic hemiparetic stroke patients. Written informed consents were obtained from 10 healthy subjects (mean age 25.8±6.8 years), who underwent two scans in one session plus the third scan one week later, and from 15 patients (mean age 47.5±9.1 years, 6–60 months after the onset of stroke, NIHSS scores between 9 and 20) who were scanned thrice on separate days within one month. Diffusion-tensor imaging was performed at 3T with 25 diffusion directions. Corticospinal tracts were reconstructed using fiber assignment by continuous tracking without and with motion/eddy-current corrections. Intra- and inter-rater as well as intra- and inter-session variations of the DTT derived indices (fiber number, apparent diffusion coefficient (ADC), and fractional anisotropy (FA)) were assessed. Intra-session and inter-session coefficients of variations (CVs) are small for FA (1.13–2.09%) and ADC (0.45–1.64%), but much larger for fiber number (8.05–22.4%). Inter-session CVs in the stroke side of patients (22.4%) are higher than those in the normal sides (18.0%) and in the normal subjects (14.7%). Motion/eddy-current correction improved inter-session reproducibility only for the fiber number of the infarcted corticospinal tract (CV reduced from 22.4% to 14.1%). The fiber number derived from corticospinal DTT shows substantially lower precision than ADC and FA, with infarcted tracts showing lower reproducibility than the healthy tissues.